‘Experts’, Settlers and Africans: the production of local agricultural knowledge in early colonial Zimbabwe - Gargallo, E. (8th European Conference on African Studies ECAS2019, 2019)
The aim of this paper is to analyse how scientific discourse and policies dealing with crops and livestock were established in Rhodesia (present day Zimbabwe), which ideas and practices became accepted as scientifically sound, and, therefore, how ‘local’ agricultural knowledge was developed in early colonial times.